Systematic review and meta-analysis of uniportal versus multiportal video-assisted thoracoscopic lobectomy for lung cancer - Harris, Christopher G.; James, Rebecca S.; Tian, David H.; Yan, Tristan D.; Doyle, Mathew P.; Gonzalez-Rivas, Diego; Cao, Christopher (Annals of Cardiothoracic Surgery; Vol 5, No 2 (March 01, 2016): Uniportal Video-Assisted Thoracoscopic Lobectomy, 2016)
Background: Uniportal video-assisted thoracoscopic surgery (VATS) has emerged as a less invasive alternative to the conventional multiportal approach in the treatment of lung cancer. The benefits of this uniportal technique have not yet been characterized in patients undergoing VATS lobectomy. This meta-analysis aimed to compare the clinical outcomes of uniportal and multiportal VATS lobectomy for patients with lung cancer. Methods: A systematic review was conducted using seven electronic databases. Endpoints for analysis included perioperative mortality and morbidity, operative time, length of hospital stay, perioperative blood loss, duration of postoperative drainage and rates of conversion to open thoracotomy. Results: Eight relevant observational studies were identified and included for meta-analysis. Results demonstrated a statistically significant reduction in the overall rate of complications, length of hospital stay and duration of postoperative drainage for patients who underwent uniportal VATS lobectomy. There were no significant differences between the two treatment groups in regard to mortality, operative time, perioperative blood loss and rate of conversion to open thoracotomy. Conclusions: The present meta-analysis demonstrated favourable outcomes for uniportal VATS lobectomy in the treatment of lung cancer compared to the conventional multiportal approach. However, long-term follow-up data is still needed to further characterize the benefits of the uniportal approach.